Leitlinie der European Society of Cardiology zum chronischen Koronarsyndrom von 2024 - Achenbach, Stephan (Herz, 2025)
The 2024 European Society of Cardiology (ESC) guidelines on chronic coronary syndrome comprehensively summarize the symptoms, diagnostics and treatment of coronary artery disease, excluding acute coronary syndromes. The processing always begins with an estimation of the clinical probability, which should include not only the symptom profile but also the number of cardiovascular risk factors and is further modified by any conspicuous findings in electrocardiography (ECG), exercise testing, or echocardiography. For further diagnostics, coronary angiography via computed tomography is the first-line approach if the probability lies between 5% and 50%. For probabilities of 50-85% procedures for imaging-based ischemia detection are indicated, while for even higher probabilities immediate invasive diagnostics are given priority. The treatment includes intensive risk modification, medicinal anti-anginal treatment and finally revascularization by coronary intervention or bypass surgery. In the absence of high-risk constellations a medication-based approach should be initially preferred, with revascularization indicated if symptoms persist. The new guidelines also extensively address angina and ischemia without obstructive coronary lesions. In this context, intensive risk modification and initial medication treatment are again recommended.
EVALuna2:583811